What drives the failure of private participation in infrastructure projects?. Issue 6 (28th May 2020) - Ruiz Díaz, Gonzalo
Abstract : Purpose: The purpose of this paper is to assess the determinants of the early termination of infrastructure projects implemented under public–private partnerships (PPP), concessions or privately managed divested assets. Design/methodology/approach: Cross-section and duration model estimations were applied to a sample of 2, 655 infrastructure projects implemented in Latin America and the Caribbean for the period 1993–2017. Estimation techniques consist of a logistic model and cox proportional hazards model (CPHM) applied to alternative specifications, including diverse causal factors. Findings: Evidence is found that early termination of infrastructure projects is determined by intrinsic and extrinsic factors. Among the intrinsic factors, the main characteristics of projects that increase the likelihood of failure are the size or scale of the project, the sector in which the project is developed (transport and water and sanitation) and being investments in divested assets. Extrinsic factors that showed a negative impact on the risk of early termination are good regulatory quality and domestic macroeconomic stability. Likewise, external real and financial shocks also contribute importantly to explain the likelihood of early termination of infrastructure projects. Practical implications: The results reveal that particular care must be put in design and supervision of large-scale projects, either in transport or water and sanitation. As well, risks associated with external shocks must be explicitly acknowledged in project design, with appropriate remedies and safeguards. The prevalence of relatively high rates of early termination in projects in divested assets in contrast with PPP suggests the importance of introducing simpler way out mechanisms for concessionaires. Finally, the results show the key importance of institutional factors like regulatory quality in determining project failure on economic performance of infrastructure projects. Originality/value: In contrast to the previous literature, the analysis shows the decisive role played by financial external factors and institutional factors of Latin American and Caribbean countries in early termination of private participation in infrastructure projects. As well, the finding of a higher likelihood of failure in projects that involve investments in divested assets versus concession or PPP suggests the need of investigate further the tradeoffs regarding the balance that must exist among guarantees offered to investors in infrastructure projects and the need to keep contractual decisions in line with market signals.